Analysis of Changes in Scalp Skin Thickness According to Age and Sex Based on Ultrasonography and Histometry - Kunyong Sung; Seung Ho Lee; Suk Joon OH; Chanho Jeong; Jeong Tae Kim; Jong Dae Kim (Archives of Plastic Surgery)
Background This study investigates scalp skin thickness using ultrasonography and histometry, exploring its relationship with age and sex. Methods The study data were obtained from split-thickness skin grafting using hairy scalp skin as the donor site in 102 Korean patients. The skin thickness of the donor scalps was measured using preoperative ultrasound in all 102 patients, and the histometric thickness of a 3 mm punch biopsy near the donor site was measured in 61 patients postoperatively. The scalp skin thickness was statistically analyzed according to age and sex. Results The mean ultrasonographic thickness was 1.71 ± 0.41 mm, while the mean histometric thickness was 1.93 ± 0.47 mm. The difference was statistically significant (P < 0.001). Regression analysis showed a significant relationship between ultrasonographic scalp skin thickness and age, but not sex. Thickness increased up to 20 years, with no significant change beyond that. Conclusions Scalp skin thickness correlates with age, but not sex. Preoperative ultrasonography is crucial for assessing scalp skin thickness, especially for younger patients under 21 years, to optimize scalp grafting outcomes.